Long-term Outcomes in Patients Undergoing Liver Transplantation for Nonalcoholic Steatohepatitis-Related Cirrhosis. Issue 8 (August 2017) - Bhati, Chandra; Idowu, Michael O.; Sanyal, Arun J.; Rivera, Maria; Driscoll, Carolyn; Stravitz, Richard T.; Kohli, Divyanshoo R.; Matherly, Scott; Puri, Puneet; Gilles, HoChong; Cotterell, Adrian; Levy, Marlon; et al.
Abstract : Background: Nonalcoholic steatohepatitis (NASH), a clinically aggressive variant of nonalcoholic fatty liver disease (NAFLD), is becoming an increasingly common indication for liver transplantation (LT); however, relatively little is known regarding its clinical course post-LT. The aim of the current study is to describe disease recurrence and clinical course after LT. Methods: All surviving patients transplanted for NASH at the authors' institution had transient elastography (TE) to evaluate hepatic steatosis and fibrosis. The charts of deceased patients were reviewed for liver biopsy to evaluate for disease recurrence. Finally, causes of mortality in these patients were evaluated. Results: Of the 103 patients who met criteria, 56 had TE, whereas 34 had a liver biopsy. Steatosis was detected in 49 (87.5%) of the patients who had a TE and were defined to have recurrent NAFLD. Most patients had liver stiffness measurements consistent with no fibrosis (42.9%) or F1-F2 fibrosis (30.4%). Advanced fibrosis was noted in 26.8%, whereas 5.4% had cirrhosis but were clinically compensated. In patients with liver biopsy, 88.2% had recurrent NAFLD, whereas 41.2% had recurrent NASH. Bridging fibrosis was noted in 20.6% of patients but no patients had cirrhosis. Within the cohort, 32 patients died with the leading cause of mortality cancer (25%), infectious complications (25%), and cardiovascular disease (21.9%). Only 9% of deaths were attributable to graft cirrhosis. Conclusions: Recurrent NAFLD is common post-LT occurring in nearly 88% of all patients, whereas nearly a quarter of patients were noted to have advanced fibrosis. Abstract : A single-center study describing disease recurrence and clinical course after liver transplantation in a series of surviving patients transplanted for nonalcoholic steatohepatitis. Supplemental digital content is available in the text.